1999
DOI: 10.1055/s-1999-13532
|View full text |Cite
|
Sign up to set email alerts
|

Therapieergebnisse nach primär konservativer Versorgung distaler Radiusfrakturen bei Patienten im Alter von über 65 Jahren

Abstract: In old-aged patients with distal radius fractures, the indication for surgical treatment should be made very carefully, since certain degrees of radiological malalignment are tolerated well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Kelly, Warwick, Crichlow et al (1997) felt that for patients more than 65 years old a maximum of 30° of dorsal angulation and 5 mm of radial shortening could be accepted. Jacob, Mielke, Keller et al (1999) found that a dorsal angle of more than 20° and a radial inclination of less than 15° were associated with more complaints and patient dissatisfaction. Treatment guidelines have also been advanced for distal radius fractures based on the anatomic deformity.…”
Section: Discussionmentioning
confidence: 94%
“…Kelly, Warwick, Crichlow et al (1997) felt that for patients more than 65 years old a maximum of 30° of dorsal angulation and 5 mm of radial shortening could be accepted. Jacob, Mielke, Keller et al (1999) found that a dorsal angle of more than 20° and a radial inclination of less than 15° were associated with more complaints and patient dissatisfaction. Treatment guidelines have also been advanced for distal radius fractures based on the anatomic deformity.…”
Section: Discussionmentioning
confidence: 94%
“…Die rein kon ser va ti ve Be hand lung [7] ist ins be son de re auf grund der ver bes serten ope ra ti ven Mög lich kei ten nur noch bei sta bi len Frak tu ren (Typ A2 nach der AO-Klas si fi ka ti on) zu emp feh len. Hauptgrund ist die hohe Re dis lo ka ti ons nei gung der in sta bi len Frak tu ren (A3, C1-C3), auch bei suf fi zi en ter Nach be hand lung.…”
Section: Dis Kus Si Onunclassified
“…Distal radius fracture is one of the most common fractures seen in Accident and Emergency departments (Jedwabinski et al, 1996;Jupiter, 1991;Kedra and Pielka, 1998;Skowronski, 2003). In most cases, it is managed conservatively with primary closed reduction under local or regional anaesthesia and then immobilization in plaster of Paris (Altissimi et al, 1986;Bacorn and Kurtzke, 1953;Earnshaw et al, 2002;Jakob et al, 1999;Kedra and Pielka, 1998;Lindstrom, 1959;Porter and Stocklej, 1987;Sarmiento et al, 1980;Skowronski, 2003;Toh and Jupiter, 1995;Young and Rayan, 2000).…”
Section: Introductionmentioning
confidence: 99%